2020
DOI: 10.1080/17453674.2020.1831236
|View full text |Cite
|
Sign up to set email alerts
|

How deadly is a fracture distal to the hip in the elderly? An observational cohort study of 11,799 femoral fractures in the Swedish Fracture Register

Abstract: Background and purpose — Unlike hip fractures, diaphyseal and distal femoral fractures in elderly patients have not been widely studied. We investigated the demographics, comorbidities and mortality of patients with femoral fractures at any anatomical level with a focus on early mortality. Patients and methods — We analyzed 11,799 patients ≥ 65 years with a femoral fracture registered in the Swedish Fracture Register from 2011 to 2014. The cohort was matched with the National Patient Register to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
6
13
0
Order By: Relevance
“…It was beyond our scope to analyze the influence of comorbidities and the death cause. The mortality rate was, as expected, observed to be related to age, in accordance with previous reports of specific fracture locations such as the humerus (Ravindrarajah et al 2018, Bergdahl et al 2020) and the femur (Ravindrarajah et al 2018, Wolf et al 2021.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was beyond our scope to analyze the influence of comorbidities and the death cause. The mortality rate was, as expected, observed to be related to age, in accordance with previous reports of specific fracture locations such as the humerus (Ravindrarajah et al 2018, Bergdahl et al 2020) and the femur (Ravindrarajah et al 2018, Wolf et al 2021.…”
Section: Discussionsupporting
confidence: 92%
“…Proximal femur fractures had the highest mortality rate among all fracture locations; 25% at 1 year with a corresponding SMR of 2.7, which is in accordance with previous studies (Vestergaard et al 2007b, Gundel et al 2020. For comparison, distal femur fractures had a 30-day mortality rate of 4.8%, which is similar to the 5% mortality reported by Larsen et al (2020) and 6.3% by Wolf et al (2021). The 18% 1-year mortality for distal femur fracture patients in our study was lower than the 25% for proximal femur fractures, with a similar SMR of 2.7.…”
Section: Discussionsupporting
confidence: 87%
“…Earlier comparisons of mortality rates between hip and non-hip femur fractures either found similar rates (Streubel et al 2011 ) or higher mortality rates for hip fractures, as found in our study (Deakin et al 2007 , Abrahamsen et al 2009, Wolf et al 2020 ). A Finnish study compared 30- and 90-day, mortality rates between patients with hip and pelvic fracture and found no differences (Reito et al 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…Reports on long-term mortality after femur shaft fracture are scarce, especially among older patients. A recent Swedish study investigated mortality in femur shaft fractures among patients ≥ 65 years and found a 1-year mortality of 21%, as in our study (Wolf et al 2020 ). A German study investigating high-energy femur shaft fractures among young and middle-aged adults reported an in-hospital mortality of 10% (Kobbe et al 2013 ).…”
Section: Discussionsupporting
confidence: 81%
“…Although people over the age of 65 were restricted from going out to the streets, intertrochanteric femur fractures (IFFs) frequently continued in elderly patients due to low-energy trauma such as simple falls. IFFs are an important factor affecting mortality and morbidity in this patient group because elderly patients are often accompanied by comorbidities [ 3 ]. While IFFs were treated during the pandemic, COVID-19 positive patients were operated on in negative-pressure operating rooms and the surgical team entered surgery with personal protective equipment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%